Allicin Inhibits Osteosarcoma Growth by Promoting Oxidative Stress and Autophagy via the Inactivation of the lncRNA MALAT1-miR-376a-Wnt/β-Catenin Signaling Pathway. (24th June 2022) - Xie, Wenpeng; Chang, Wenjie; Wang, Xiaole; Liu, Fei; Wang, Xu; Yuan, Daotong; Zhang, Yongkui
Abstract : Allicin, an organic sulfur compound extracted from the bulb of Allium sativum, can potentially prevent various tumors. Our previous study found that allicin can effectively suppress the proliferation of osteosarcoma cells. However, the molecular mechanisms have not been illustrated. In this study, Saos-2 and U2OS osteosarcoma cells were used to investigate the underlying mechanisms. A series of experiments were carried out to authenticate the anticancer property of allicin. Knockdown of lncRNA MALAT1 inhibited the proliferation, invasion and migration and promoted apoptosis of osteosarcoma cells. Knockdown of miR-376a increased the proliferation, invasion, and migration and dropped apoptosis of osteosarcoma cells. Furthermore, knockdown of miR-376a reversed the influences of MALAT1 silencing in osteosarcoma cells. Based on our data, MALAT1 could downregulate the expression of miR-376a, subsequently accelerating osteosarcoma. Moreover, oxidative stress and autophagy were identified as the potential key pathway of allicin. Allicin inhibited osteosarcoma growth and promoted oxidative stress and autophagy via MALATI-miR-376a. We also found that allicin promotes oxidative stress and autophagy to inhibit osteosarcoma growth by inhibiting the Wnt/ β -catenin pathway in vivo and in vitro . All data showed that allicin promotes oxidative stress and autophagy of osteosarcoma via the MALATI-miR-376a-Wnt/ β -catenin pathway.